2019
DOI: 10.1002/jgc4.1109
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling for consumer‐driven whole exome and whole genome sequencing: A commentary on early experiences

Abstract: Counseling after consumer‐driven whole exome sequencing (WES) and whole genome sequencing (WGS) presents challenges for genetic counselors as availability of this testing increases. There are no standard practice guidelines and limited resources for genetic counselors in this area, but consumer demand for counseling and data interpretation exists and is likely to grow along with testing opportunities. In this paper, we comment upon our experiences as three independent, private practice genetic counselors who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Understanding clients’ motivations, what they hope to understand and learn was similarly stressed by Schmidt et al. (2019).…”
Section: Participant (P#) Sex Age At Testing Participant Had Childrenmentioning
confidence: 90%
See 3 more Smart Citations
“…Understanding clients’ motivations, what they hope to understand and learn was similarly stressed by Schmidt et al. (2019).…”
Section: Participant (P#) Sex Age At Testing Participant Had Childrenmentioning
confidence: 90%
“…Although this high proportion likely reflects bias of ascertainment and has not been reported before in DTC studies, this is a population where DTC testing may be of particular interest given their diagnostic challenges. Of relevance, Schmidt, Mass, and Altmeyer (2019) found that one‐third of their clients who sought genetic counseling for consumer‐driven whole exome (WES) and whole genome sequencing (WGS) were “undiagnosed and searching” and several of the symptoms they listed are seen with EDS Type III (e.g., joint pain, chronic fatigue, digestive problems).…”
Section: Participant (P#) Sex Age At Testing Participant Had Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the participant feedback also suggests a need to consider alternatives to traditional service delivery models and flexibility in the content and length of genetic counseling services, which should be considered strongly by counselors providing services for personalized medicine patients. Schmidt et al (2019) present data from 70 patients seen over the course of 2 years for genetic counseling following exome or genome sequencing. Similar to Sweet et al the counselors followed a Reciprocal Engagement Model for their counseling, allowing the client to set the priorities of the session throughout.…”
Section: Genetic Counseling: the Keystonementioning
confidence: 99%